A review of dermal melanocytosis - Manjyot Gautam; Kajomi Shingala (Wolters Kluwer Medknow Publications, 2023)
Dermal melanocytosis is a histological term used to describe a clinical spectrum of cutaneous diseases which present as bluish-gray pigmentation of the skin. The most common forms include the Mongolian spot (MS), nevus of Ota, nevus of Ito, and dermal melanocyte hamartoma sharing similar etiologies and histologic findings but different associations and prognosis. Although these lesions usually resolve by 1 to 2 years of age, widespread aberrant MSs, nevus of Ota, and nevus of Ito can persist into adulthood and can become a great concern for the patients regarding the pigmentation and health risk associated with the same. An extensive literature search was done; all clinical trials, randomized double-blind or single-blind controlled trials, open-label studies, retrospective studies, reviews, case series, and case reports concerned with dermal melanocytosis were screened. The selected articles were retrieved; the final manuscript was prepared, analyzed, and presented in a narrative fashion.